Signaling Theory: A Review and Assessment - Connelly, Brian L.; Certo, S. Trevis; Ireland, R. Duane; Reutzel, Christopher R. (Journal of Management, 2011)
Signaling theory is useful for describing behavior when two parties (individuals or organizations) have access to different information. Typically, one party, the sender, must choose whether and how to communicate (or signal) that information, and the other party, the receiver, must choose how to interpret the signal. Accordingly, signaling theory holds a prominent position in a variety of management literatures, including strategic management, entrepreneurship, and human resource management. While the use of signaling theory has gained momentum in recent years, its central tenets have become blurred as it has been applied to organizational concerns. The authors, therefore, provide a concise synthesis of the theory and its key concepts, review its use in the management literature, and put forward directions for future research that will encourage scholars to use signaling theory in new ways and to develop more complex formulations and nuanced variations of the theory.